Adaptive Gelatin Microspheres Enhanced Stem Cell Delivery and Integration With Diabetic Wounds to Activate Skin Tissue Regeneration - Shi, Ming; Gao, Yunfen; Lee, Lim; Song, Ting; Zhou, Jianhua; Yan, Ling; Li, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
The delayed and complicated diabetic wound healing raises clinical and social concerns. Application of stem cells along with hydrogels is an attractive therapeutic approach. However, low cell retention and integration hindered the performance. Herein, gelatin microspheres were fabricated for local delivery of adipose-derived stem cells (from rats, rADSCs), and the effect of rADSCs with microspheres on diabetic wound healing was examined. Uniform well-dispersed microspheres were fabricated using microfluidic technique. Due to geometry difference, the proteinase degradation rate for microspheres was 4 times that of the bulk hydrogel. The obtained gelatin microspheres supported cells adhesion and proliferation as well as provided a suitable microenvironment for rADSCs survival. For in vivo animal tests, rADSCs were labeled with CM-Dil for tracking purpose. Microspheres were well embedded in the regenerated tissue and demonstrated a good biocompatibility and an adaptive biodegradation rate. Histological examination revealed rADSC/MS significantly accelerated wound healing via promoting M2 macrophages polarization, collagen deposition, angiogenesis associated with peripheral nerve recovery, and hair follicle formation. Notably, the relative fluorescence intensity around hair follicle was 17-fold higher than that of blank group, indicating rADSC participated the healing process via exosomes. Taken together, the rADSC-laden gelatin microspheres provided a promising strategy for local stem cell delivery to improve diabetic wound healing.